Utilization of Clinoptilolite Zeolite to Reduce P-Phenylenediamine (PPD) Dye Content from Hair Color Wash Waste - Rahmadani, Rara; Zilfa, Z; Wendari, Tio Putra (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Environmental pollution is a global problem that requires serious attention worldwide. Various human activities contribute to increased levels of pollutants, including liquid waste. One example is the hair colouring process, which generates waste that is harmful to both the environment and human health. This waste contains explicitly hazardous components such as synthetic dyes, for example, p-phenyldiamine dyes. Therefore, this study aims to utilise zeolite clinoptilolite (an adsorbent) for the absorption or removal of dyes in hair dye wash water waste. Based on the parameters of the dye content contained in the waste to determine the effect of adsorbent mass, contact time and concentration on the adsorption process. Determination of dye adsorption capacity using UV-VIS spectrophotometry. FTIR and XRD characterized Zeolite before and after adsorption. This study shows that adsorption lasts for 45 minutes using 0.6 grams of zeolite, with a dye sample volume of 20 mL for dye absorption. After the adsorption process at optimal conditions, the per cent adsorption of hair dye wash water waste was 81.78%. Analysis of the zeolite before and after adsorption using FTIR revealed a change in the spectrum, characterised by a shift in wavenumbers, indicating that the adsorption process had occurred. Characterization of zeolite using XRD showed that there was no change in zeolite structure. From these data, it can be concluded that the adsorption method can reduce the content of dyes in hair dye.     Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water SDG 11: Good Health and Well-beingSDG 13: Industry, Innovation, and InfrastructureSDG 15: Climate Action